A method for the preparation and characterization of single molecular weight urethane oligomers: A preliminary ion mobility and mass spectrometry study. (16th January 2023) - May, Jody C.; Tomlinson, Ian D.; Soni, Sahil; McLean, John A.; Hercules, David M.
Abstract: Commercial polyurethanes (PURs) are produced on the industrial scale by reacting methylene diphenyl diisocyanate (MDI) with low MW polyols which are distributions of multiple individual diols. Thus, the resulting PUR oligomers consist of a mixture of structural isomers at each discrete mass in the distribution. The contribution of specific isomers can be studied by starting with monodisperse, structurally-pure polyols, however this approach becomes intractable for larger MW polyols, which are challenging to synthesize and purify. Here we demonstrate a straightforward synthesis approach for generating PUR oligomer distributions with unique numbers of polyol attachments. Four readily-available, low MW polyols (PEG, PPG, PTHF, and PBA) were reacted with phenyl isocyanate (PhNCO) to produce distributions of PUR oligomers exhibiting unique numbers of polyol attachments. Structural characterization by ion mobility (IM) and high resolution mass spectrometry (HRMS) confirmed these PUR oligomers are of a single measurable structure and unique mass, and tandem MS/MS results indicated the oligomer products follow known fragmentation mechanisms. Graphical abstract: Reaction of a polydisperse polyol with phenyl isocyanate yields distributions of urethane olgomers. Image 1 Highlights: A straightforward synthesis method to generate various urethane oligomers with single molecular weights. Characterization by mass spectrometry and ion mobility indicate urethane oligomers are monodisperse in mass and structure. The synthesis of single molecular weight urethanes provides the basis for studying larger polyurethane systems.